The Global Economic Impact of UTAUT: A Bibliometric Analysis - Utama, Satria Putra; Rachmadi, Kartika Rose; Sari, Risca Kurnia (IQTISHODUNA, 2025)
This study explores the global economic impact of the Unified Theory of Acceptance and Use of Technology (UTAUT) through a bibliometric and thematic analysis. By examining 561 publications from the Scopus database over the past two decades (2004-2025), the research identifies publication trends, author collaborations, and the contributions of institutions and countries to UTAUT scholarship. Key findings reveal that UTAUT has evolved from a technology adoption theory into a multidisciplinary framework influencing the digital economy and education sectors. The thematic analysis highlights four core themes: technological innovation, user behavior, digital transformation, and economic development. This study offers strategic insights for researchers and policymakers to leverage UTAUT in technological development and data-driven decision-making. The results emphasize the significance of cross-country and cross-sector collaboration in expanding the global application of UTAUT